Verfahren zur Charakterisierung des Niederfrequenzverhaltens von Lithium-Ionen Batterien - Schönleber, Michael (Schriften des Instituts für Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Angewandte Materialien - Werkstoffe der Elektrotechnik, 2017)
In order to understand the current-voltage behaviour of a Lithium-Ion Battery, its impedance needs to be investigated in the low-frequency domain. This work deals with measurement, modelling and model validation in that low-frequency domain and introduces the Distribution-Function-of-Differential-Capacity (DDC) as a new tool for investigating capacity contributions of different particle sizes and particle types inside of a Lithium-Ion Battery.